1996
DOI: 10.3168/jds.s0022-0302(96)76586-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Action of Lactobacillus acidophilus ATCC 43121 and Calcium in Swine with Hypercholesterolemia Induced by Diet

Abstract: Thirty-three Yorkshire barrows (92 kg), fed a high cholesterol diet for 14 d had mean concentrations of serum cholesterol of 294.6 +/- 7.8 mg/dl. Starting on d 15 and for an additional 15 d, crystalline cholesterol was removed from the diet and pigs were assigned to one of four treatments: including two levels of calcium (0.7% and 1.4%) with and without added viable Lactobacillus acidophilus ATCC 43121 (2.5 x 10(11) cells per feeding). Serum cholesterol levels decreased, as expected, for all groups. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
2
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(82 citation statements)
references
References 33 publications
4
70
2
6
Order By: Relevance
“…Our study indicated that the rats fed on a high-carbohydrate diet and supplemented with L. casei strain Shirota had a decrease in their serum glucose levels. However, the rats fed on a highlipid diet did not show changes in serum cholesterol or triglyceride levels 38 . Wang et al suggested that L. plantarum MA2 decreased serum levels of total cholesterol, LDL cholesterol and triglyceride levels in rats fed on high-cholesterol diets 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that the rats fed on a high-carbohydrate diet and supplemented with L. casei strain Shirota had a decrease in their serum glucose levels. However, the rats fed on a highlipid diet did not show changes in serum cholesterol or triglyceride levels 38 . Wang et al suggested that L. plantarum MA2 decreased serum levels of total cholesterol, LDL cholesterol and triglyceride levels in rats fed on high-cholesterol diets 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus acidophilus is the best studied of the`probiotic' cholesterol-lowering bacteria (Lin et al, 1989;Schaafsma et al, 1998;Harrison & Peat, 1975;Khedkar et al, 1993;de Rodas et al, 1996). Of all the Lactobacillus acidophilus-strains the L-1 strain, used in commercial products in the Netherlands, is thought to be one of the most effective strains to lower serum cholesterol (Buck & Gilliland, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The bile acid and cholesterol level in feces of the mice fed with yoghurt and probiotic bacteria (groups C & D) were higher than those of group B with highest concentration in group C. As deconjugated bile salts are more readily excreted in the feces than conjugated bile salts [37][38][39], bacteria with BSH activity may effectively reduce serum cholesterol by enhancing the excretion of bile salts, with a consequent increase in the synthesis of bile salts from serum cholesterol; or by decreasing the solubility of cholesterol, since bile acid is essential for gastrointestinal absorption of cholesterol [6] and thus reducing its uptake from the gut.…”
Section: Bile Acid and Cholesterol Concentration In Fecesmentioning
confidence: 97%